Do litoral ao interior: um estudo sobre o léxico de origem indígena em comunidades do semiárido baiano - Ferreira, Saádia Ramos (2024)
Studying the lexicon of a language is knowing the history and culture of a people, as the lexicon is the representation of the culture and identity of a community. Lexicon studies are carried out on three main subjects: lexicology, lexicography and terminology. This work is based on the principles of lexicography, which is the science responsible for describing and recording the lexicon, through the creation of dictionaries, and sociolinguistics which studies linguistic variations, sometimes focusing on aspects of variation, and also the formation of a language. To carry out the studies developed in this work, we based on the contributions such as: Biderman (1981; 1984; 2001), Lucchesi (2009; 2012), Mattos and Silva (2004), Naro and Scherre (2007), Rodrigues (1993), Santos (2012), and others. Seeking to analyze the contributions of indigenous languages to the formation of the Brazilian Portuguese (BP) and in the lexicon of the semi-arid region of Bahia, we used the four volumes that make up the corpus Amostras da Língua Falada no Semiárido Baiano (Almeida; Carneiro, 2008), to search lexias that have their origins in indigenous languages, from the Tupi and Macro-Jê trunks. Computer programs were used to analyze the lexias found, following the principle of modern lexicography. The data identified in the material analyzed shows how much indigenous languages have contributed and left their mark on the lexicon used in the semi-arid region of Bahia and, consequently, on Brazilian Portuguese.